Variability in summer surface residence time within a West Antarctic Peninsula biological hotspot. (14th May 2018) - Kohut, Josh T.; Winsor, Peter; Statscewich, Hank; Oliver, Matthew J.; Fredj, Erick; Couto, Nicole; Bernard, Kim; Fraser, William
Abstract : Palmer Deep canyon along the central West Antarctic Peninsula is known to have higher phytoplankton biomass than the surrounding non-canyon regions, but the circulation mechanisms that transport and locally concentrate phytoplankton and Antarctic krill, potentially increasing prey availability to upper-trophic-level predators such as penguins and cetaceans, are currently unknown. We deployed a three-site high-frequency radar network that provided hourly surface circulation maps over the Palmer Deep hotspot. A series of particle release experiments were used to estimate surface residence time and connectivity across the canyon. The majority of residence times fell between 1.0 and 3.5 days, with a mean of 2 days and a maximum of 5 days. We found a highly significant negative relationship between wind speed and residence time. Our residence time analysis indicates that the elevated phytoplankton biomass over the central canyon is transported into and out of the hotspot on time scales much shorter than the observed phytoplankton growth rate, suggesting that the canyon may not act as an incubator of phytoplankton productivity as previously suggested. It may instead serve more as a conveyor belt of phytoplankton biomass produced elsewhere, continually replenishing the phytoplankton biomass for the local Antarctic krill community, which in turn supports numerous top predators. This article is part of the theme issue 'The marine system of the West Antarctic Peninsula: status and strategy for progress in a region of rapid change'.